Retrobulbar haematoma secondary to haemophilia A in a dog. Issue 3 (7th July 2021) - Amorim, Ana; Reisinho, Ana; Vicente, Gonçalo; Delgado, Esmeralda
Abstract: A 6‐year‐old male Yorkshire terrier presented due to sudden onset exophthalmos of the left eye. Ocular signs included conjunctival haemorrhage and third eyelid protusion. Physical examination revealed decreased ocular retropulsion and pain on opening the mouth. Skull CT demonstrated the presence of a retrobulbar mass. Transoral drainage of the retrobulbar space disclosed blood, but subsequently to this procedure profuse bleeding occurred from the incision site, while haematocrit levels decreased significantly. Coagulation tests showed a deficiency on the VIII and XII clotting factors, compatible with haemophilia A. As a consequence of exophthalmos, a severe exposure keratitis took place that rapidly evolved to perforation. After fresh frozen plasma administration, a transconjunctival enucleation was performed. Although uncommon, retrobulbar haematoma resulting from haemostatic defects should be included in the differential diagnosis of exophthalmos in dogs.